Gregor Mendel fut-il soumis à la corvée avant de devenir moine en 1843 ? - Nivet, Christiane (MS. Médecine sciences, 2020)
Our knowledge of the young Mendel's life prior to his admission to the monastery comes essentially from the curriculum vitae submitted in 1850. His first biographer Hugo Iltis used this document as a sort of autobiography, although the document contained various voluntary omissions and inaccuracies. We have sought the reasons for these and in so doing have discovered why Mendel's entry into religion had become ineluctable.
Keywords: příprava učitelů; Work; Social Class; Faculty; Philosophy; filozofie; Taxes; lidé; Monks; teologie; Humans; Czech Republic; práce; akademický sbor; History, 19th Century; společenská třída; Česká republika; mniši; dějiny 19. století; daně; Theology; Teacher Training